Effectiveness of Some Plant Extracts and Commercial Biological Products to Control Powdery Mildew Disease in Meniran Plants (Phyllanthus niruri) - Siregar, Brema Syahputra; Widihastuty, Widihastuty; Mazidah, Mazidah (UNIVERSITAS LABUHANBATU, 2024)
The Meniran plant (Phyllanthus niruri L.) is a herbal plant that can boost the immune system. One of the challenges in propagating meniran plants as therapeutic plants is the attack of powdery mildew disease produced by the pathogenic fungus Oidium phyllanthi. This study was conducted to determine the efficacy of different plant components and commercial biological agents in reducing powdery mildew disease on green meniran plants (Phyllanthus niruri L.). This study employs a non-factorial randomised group design (RAK) with ten treatments and three duplicates. The findings revealed that no therapy was able to prevent or diminish the occurrence of powdery mildew disease on (Phyllanthus niruri L.).In the nursery, the application of garlic extract and commercial product B'Green® Neem Oil reduced the severity of powdery mildew disease by 57.3% and 50.0%, respectively, and on B'Green® Neem Oil by 26.1% on (Phyllanthusniruri L.), whereas in the field, the application of garlic extract reduced the severity of powdery mildew disease by 27.3%, 26.2%, and on B'Green® Neem Oil by 25.0%. Keywords: Green meniran (Phyllanthus niruri), garlic, ginger rhizome, neem leaves, betel leaves